The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0003319716662424
|View full text |Cite
|
Sign up to set email alerts
|

Celiac and Superior/Inferior Mesenteric Angioplasty and Stenting for Chronic Mesenteric Ischemia: A Single-Center Experience

Abstract: Angioplasty and stenting emerged as the less invasive treatment options compared to open surgical revascularization for the management of patients with chronic mesenteric ischemia (CMI). However, endovascular techniques may not achieve symptomatic relief in many patients with CMI. We report our results from the endovascular management of patients with CMI. Data were reviewed from 45 patients undergoing celiac and/or mesenteric angioplasty and stenting for CMI, from October 2006 to January 2016. Angioplasty and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Compared with previous analyses focusing on comparative data between open and endovascular CMI repair, this systematic review aimed to assess endovascular repair Heterogeneity: τ 2 = 0; Chi 2 = 0.13, df = 6 (p = 1.0); I 2 = 0% 500 Total (fixed effect, 95% CI) Total (random effects, 95% CI) Heterogeneity: τ 2 = 0.5179; Chi 2 = 2.35, df = 7 (p = .94); I 2 = 53% 724 Total (fixed effect, 95% CI) Total (random effects, 95% CI) Allen, et al 1996 15 Sarac, et al 2008 17 Dias, et al 2010 18 Schoch, et al 2011 21 Turba, et al 2012 22 Thomas, et al 2016 26 Zacharias, et al 2016 27 Rajaratnam, et al 2016 28 Haben, et al 2020 29 Brown, et al 2005 16 Peck, et al 2010 19 Fioole, et al 2010 20 AbuRhama, et al 2013 23 Oderich, et al 2013 24 Grilli, et al 2014 25 Girault, et al 2021 30 Figure 3. Forest plot of 30 day death in patients with chronic mesenteric ischaemia managed by percutaneous endovascular repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with previous analyses focusing on comparative data between open and endovascular CMI repair, this systematic review aimed to assess endovascular repair Heterogeneity: τ 2 = 0; Chi 2 = 0.13, df = 6 (p = 1.0); I 2 = 0% 500 Total (fixed effect, 95% CI) Total (random effects, 95% CI) Heterogeneity: τ 2 = 0.5179; Chi 2 = 2.35, df = 7 (p = .94); I 2 = 53% 724 Total (fixed effect, 95% CI) Total (random effects, 95% CI) Allen, et al 1996 15 Sarac, et al 2008 17 Dias, et al 2010 18 Schoch, et al 2011 21 Turba, et al 2012 22 Thomas, et al 2016 26 Zacharias, et al 2016 27 Rajaratnam, et al 2016 28 Haben, et al 2020 29 Brown, et al 2005 16 Peck, et al 2010 19 Fioole, et al 2010 20 AbuRhama, et al 2013 23 Oderich, et al 2013 24 Grilli, et al 2014 25 Girault, et al 2021 30 Figure 3. Forest plot of 30 day death in patients with chronic mesenteric ischaemia managed by percutaneous endovascular repair.…”
Section: Discussionmentioning
confidence: 99%
“…Total (fixed effect, 95% CI) Total (random effects, 95% CI) Allen, et al 199615 Sarac, et al 200817 Dias, et al 201018 Schoch, et al 201121 Turba, et al 201222 Thomas, et al 201626 Zacharias, et al 201627 Rajaratnam, et al 201628 Haben, et al 202029 Brown, et al 200516 Peck, et al 201019 Fioole, et al 201020 AbuRhama, et al 201323 Oderich, et al 201324 Grilli, et al 201425 Girault, et al 2021 30 GLMM, fixed + random, 95% CI GLMM, fixed + random, 95% CI…”
mentioning
confidence: 99%
“…6 Endovascular treatment (ET) is the preferred therapy for elderly patients with multiple comorbidities, because of the lower perioperative mortality and shorter hospitalization. [7][8][9] However, its patency rate, symptom relief, recurrence rate, and reintervention rate, especially for low-risk patients, are not well defined when compared with OSR. Several studies have reported that patients with CMI treated with ET appeared to have a higher incidence of symptom recurrence and have recommended ET as a bridge to OSR in nutritionally depleted patients with CMI.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective case series, in a previous issue of Angiology , the authors 1 describe their 10-year institutional experience with endovascular therapy for chronic mesenteric ischemia (CMI). In addition to achieving technical success in each case, they report complete resolution of symptoms in 65% of patients and improved symptoms in an additional 13%.…”
mentioning
confidence: 99%
“…17 This is an important consideration given the results of open reconstruction in capable hands. 18 The authors of this study 1 note that follow-up details were not available for the entire cohort, with 3 patients having stent occlusion. These results highlight the importance of close follow-up and specific attentiveness to the potential for restenosis in patients with CMI who undergo endovascular treatment.…”
mentioning
confidence: 99%